Karakteristik Pie Susu Berbahan Dasar Terigu dan Tepung Millet (Panicum miliaceum L.) Kecambah Terfermentasi - Darani, Ni Made Marsya; Kartika Pratiwi, I Desak Putu; Arihantana, Ni Made Indri Hapsari (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2025)
Milk pie is a pastry product made from low-protein wheat flour, shaped thin and round, and baked. It consists of a crust and a filling, where the crust is dense and crumbly, while the filling is sweet and soft. The main ingredient for the crust is low-protein wheat flour. The use of fermented sprouted millet flour (TMKF) offers an alternative to reduce reliance on wheat flour in milk pie production. This study aimed to evaluate the characteristics of milk pie made with different ratios of wheat flour and TMKF and to determine the optimal formulation with acceptable sensory properties. A completely randomized design was used with five treatments (100:0, 90:10, 80:20, 70:30, and 60:40), each replicated three times. Data were analyzed using ANOVA, followed by Duncan’s Multiple Range Test (DMRT) when significant effects were observed. The results showed that the ratio of wheat flour to TMKF significantly affected moisture, protein, crude fiber, tannin content, and sensory attributes (color, aroma, taste, and texture). Higher TMKF levels increased protein and fiber content. The 80:20 wheat flour to TMKF formulation produced a milk pie with desirable sensory qualities, containing 19.22% moisture, 7.11% protein, 2.27% crude fiber, and 0.16% tannin, with a yellowish-brown color, non-bitter taste, and slightly less crumbly texture. Keywords: milk pie, wheat flour, fermented sprouted millet flour